Pendekatan Culturally Responsive Teaching (CRT) dalam Peningkatan Kemampuan Berpikir Kritis Siswa Kejuruan Kuliner - Luthfi Novela; Yunus Karyanto; Lailatul Firman Dyah Maulya; Dwi Apriliani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to investigate the application of the Culturally Responsive Teaching (CRT) approach in enhancing learning outcomes and critical thinking skills of vocational high school students in the culinary department, specifically in the subject of Indonesian Cake and Pastry Production (PCKI) on the topic of Indonesian cake classification. The research employed a pre-experimental design with a one group pre-test post-test model, involving 33 students of class XI WU PB at SMKN 1 Buduran, East Java. Data were collected through essay tests and observation questionnaires, analyzed using percentage of learning mastery and critical thinking level qualification techniques. The results showed an increase in classical mastery from 45.4% in the pre-cycle to 60.6% in cycle I and 78.8% in cycle II. Critical thinking skills also improved, with the percentage of students in the